Association of selenium intake with bone mineral density and osteoporosis: the national health and nutrition examination survey - Peng, Shiyu; Zhang, Gaoxiang; Wang, Decheng (Frontiers in Endocrinology, 2023)
Background: Osteoporosis (OP) is a systemic metabolic skeletal disorder characterized by a decrease in bone mineral density (BMD) and an increase in the risk of fracture. The level of selenium (Se) in serum is associated with BMD. However, the relationship between dietary and total selenium intake and parameters such as osteoporosis and BMD is unclear. By conducting National Health and Nutritional Examination Surveys (NHANES), in this study, we assessed the association of Se intake with BMD and the risk of OP among general middle-aged and elderly people.